2015
DOI: 10.1016/j.neuropsychologia.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Tracking lexical consolidation with ERPs: Lexical and semantic-priming effects on N400 and LPC responses to newly-learned words

Abstract: a b s t r a c tNovel words can be recalled immediately and after little exposure, but require a post-learning consolidation period to show word-like behaviour such as lexical competition. This pattern is thought to reflect a qualitative shift from episodic to lexical representations. However, several studies have reported immediate effects of meaningful novel words on semantic processing, suggesting that integration of novel word meanings may not require consolidation. The current study synthesises and extends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
117
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(142 citation statements)
references
References 49 publications
21
117
4
Order By: Relevance
“…Previous studies using a semantic relatedness judgment task reported a reduced negativity within N400 and/or LPC time window on new-meaning probes on the day of learning (Bakker et al, 2015; Mestres-Misse et al, 2007; Perfetti et al, 2005). Our contrasting result comes from a paradigm that minimized explicit meaning processing, raising the possibility that semantic priming effects in the previous studies could be attributed to their requirement for explicit meaning retrieval.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies using a semantic relatedness judgment task reported a reduced negativity within N400 and/or LPC time window on new-meaning probes on the day of learning (Bakker et al, 2015; Mestres-Misse et al, 2007; Perfetti et al, 2005). Our contrasting result comes from a paradigm that minimized explicit meaning processing, raising the possibility that semantic priming effects in the previous studies could be attributed to their requirement for explicit meaning retrieval.…”
Section: Discussionmentioning
confidence: 89%
“…As N400 and LPC were the main focus, we examined specifically the mean amplitudes within 300–500 ms and 500–700 ms at the central midline cluster (i.e., Cz cluster), where meaning effects are robustly observed in word learning studies (Bakker et al, 2015; Batterink & Neville, 2011; Mestres-Misse et al, 2007). For each type of trained words and meaning probes, the mean amplitude within each time window for each participant was extracted using EP Toolkit (Dien, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that new L1 words can be lexicalized very quickly after just a few learning encounters and that word-like N400 effects can be obtained from these items (e.g., Borovsky et al, 2010; Mestres-Missé et al, 2007). However, more recently Bakker et al (2015) have reported evidence that the nature of the ERP effects obtained immediately after learning are somewhat different from those where a longer period of consolidation (24 hours in their case) had taken place. Only after consolidation to new word ERPs show effects of lexicalization.…”
mentioning
confidence: 88%
“…A parallel (and larger) literature has looked at ERP changes as a function word learning in general – i.e., without telling participants the newly learned items are in a new L2 and/or using items that plausibly could be new L1 words (e.g., Bakker et al, 2015; Borovsky et al, 2010; Borovsky et al, 2012; Mestres-Missé et al, 2007; Perfetti et al, 2005) . One prominent theme in this literature is whether there is a need for a consolidation period after new words are learned in terms of their incorporation into the lexical system.…”
mentioning
confidence: 99%